2012
DOI: 10.1021/ar300177q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Covalent Chemistry on the Electronic Structure and Properties of Carbon Nanotubes and Graphene

Abstract: In this Account, we discuss the chemistry of graphitic materials with particular reference to three reactions studied by our research group: (1) aryl radical addition, from diazonium precursors, (2) Diels-Alder pericyclic reactions, and (3) organometallic complexation with transition metals. We provide a unified treatment of these reactions in terms of the degenerate valence and conduction bands of graphene at the Dirac point and the relationship of their orbital coefficients to the HOMO and LUMO of benzene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
205
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(210 citation statements)
references
References 57 publications
4
205
1
Order By: Relevance
“…Due to the specific electronic and transport properties of carbon-based nanostructures including carbon nanotube and graphene [37,38], their applications in sensing and nanoelectronics have been explored widely in recent years [39][40][41]. Of course, such investigations have also been proceeding in the field of spintronic devices with molecular nanomagnets and yielded some fascinating results especially the successful design of spin transistor and spin valves, which will be introduced in the next [43], but AFM images and molecular dynamics simulations demonstrated that those [TbPc 2 ] molecules on the surface form highly regular rectangular 2D nanocrystals, as shown in Fig.…”
Section: [Lnpc 2 ] Smms On Surfacesmentioning
confidence: 99%
“…Due to the specific electronic and transport properties of carbon-based nanostructures including carbon nanotube and graphene [37,38], their applications in sensing and nanoelectronics have been explored widely in recent years [39][40][41]. Of course, such investigations have also been proceeding in the field of spintronic devices with molecular nanomagnets and yielded some fascinating results especially the successful design of spin transistor and spin valves, which will be introduced in the next [43], but AFM images and molecular dynamics simulations demonstrated that those [TbPc 2 ] molecules on the surface form highly regular rectangular 2D nanocrystals, as shown in Fig.…”
Section: [Lnpc 2 ] Smms On Surfacesmentioning
confidence: 99%
“…It was shown [22] that the formation of hexahapto-coordinated metal ions provides new possibilities to develop new-era lowdimensional graphene and carbon nanotube materials for organometallic catalysis and spintronics by preserving the graphitic band structure during formation of bis-hexahapto-metal bonds. It was shown that a network [23] of single Cr atoms with arene ligands trapped in a periodic potential well of a graphene layer opens new possibilities to quantum routeing and state manipulation through the conductive graphene substrate.…”
Section: Introductionmentioning
confidence: 99%
“…While conventional addition chemistry in which the sp 2 -conjugated carbon atoms are rehybridized to sp 3 has been widely explored in the new carbon allotropes [4], the participation of graphene and CNTs in organometallic chemical reactions has received limited attention. The metal complexes of these carbon materials are potential candidates as reusable solid catalysts for organic synthetic applications [5], in organometallic catalysis as electronically conjugated catalyst supports [6], molecular wires [7] and new electronic materials [8,9]. Fullerenes [10][11][12][13] and CNTs [14] are curved carbon materials with demonstrated ability to serve as primary ligands, whereas graphene represents a new class of periodic, planar two-dimensional π-ligands which has been recently reported to have a rich organometallic chemistry [6], in analogy with the coordination chemistry of polyaromatic hydrocarbons (PAHs) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes [10][11][12][13] and CNTs [14] are curved carbon materials with demonstrated ability to serve as primary ligands, whereas graphene represents a new class of periodic, planar two-dimensional π-ligands which has been recently reported to have a rich organometallic chemistry [6], in analogy with the coordination chemistry of polyaromatic hydrocarbons (PAHs) [15]. The flat two-dimensional π-surface of graphene exhibits a unique chemical reactivity as a result of the electronic structure at the Dirac point and this provides the opportunity to perform a wide range of chemical reactions [6,9,16,17]. Functionalization of CNTs with transition metal complexes alters their electronic and chemical properties and single-walled carbon nanotubes (SWCNTs) have been already used as transition metal supports in heterogeneous [18][19][20] and homogeneous catalysis [5].…”
Section: Introductionmentioning
confidence: 99%